PENGARUH KEPUASAAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN DUKUNGAN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi di Dinas Kelautan dan Perikanan Kabupaten Kendal) - Joko Suprayoga, 1242020051; Setyowati, Widhy (Jurnal Mahasiswa Pasca Sarjana, 2015)
The objektive of research to: 1) Know the effect of job satisfaction on organizational citizenship behavior; 2) Determine the influence of organizational Â commitment on organizational citizenship behavior; 3) Analyze the role of percieved organizational support moderates the effect of job satisfaction on organizational citizenship behavior; 4) Analyze the role of percieved organizational support moderates the effect of organizational commitment on organizational citizenship behavior. The results of this study can contribute to development of models organizational citizenship behavior, making it useful for academics and practitioners. This study is a correlational study to examine the relationship between variables. The samples in this study were employees of the Dinas Kelautan dan Perikanan Kendal, and the data of this research is primary data derived from the question naire.The results of this study indicate that: 1) The variable job satisfaction has a positive and significant influence on organizational citizenship behavior variables, with a coefficient of 0.580 and significant at 0.000; 2) Variable of organizational commitment has a positive and Â significant influence on organizational citizenship behavior variables, with a coefficient of 0.370 and significant at 0.039; 3) Percieved organizational support as a moderating variable has a significant positive effect between job satisfaction with organizational citizenship behavior, with a coefficient of 2.072 and significant at 0.006; 4) Percieved organizational support as a moderating variable has no significant effect between organizational commitment with organizational citizenship behavior, because significant at 0.210. Keywords: job satisfaction, organizational commitment, percieved organizational support and organizational citizenship behavior.